What is the relationship between ideas in the human mind and ideas in the mind of God for Spinoza? - Lucash, Frank (Sophia, 2006)
The relation between ideas in the human mind and ideas in the mind of God in Spinoza is problematic because it is often expressed in obscure language and because Spinoza seems to be making puzzling and contradictory statements about it. I try to eliminate the problem by going from the idea that God has of himself to his idea of the essence and existence of the human mind and the human body. I then go from the idea of the essence of the human mind to the idea of the essence of other things, including God.